Cell-Mediated Immune Responses After Influenza Vaccination of Solid Organ Transplant Recipients: Secondary Outcomes Analyses of a Randomized Controlled Trial. (24th September 2019) - L'huillier, Arnaud G; Ferreira, Victor H; Hirzel, Cedric; Natori, Yoichiro; Slomovic, Jaclyn; Ku, Terrance; Hoschler, Katja; Ierullo, Matthew; Selzner, Nazia; Schiff, Jeffrey; Singer, Lianne G; Humar, Atul; et al.
Abstract: Background: Despite annual immunization, solid organ transplant (SOT) patients remain at increased risk for severe influenza infection because of suboptimal vaccine immunogenicity. We aimed to compare the CD4 + and CD8 + T-cell responses of the high-dose (HD) and the standard-dose (SD) trivalent inactivated vaccine. Methods: We collected peripheral blood mononuclear cells pre- and postimmunization from 60 patients enrolled in a randomized trial of HD versus SD vaccine (30 HD; 30 SD) during the 2016–2017 influenza season. Results: The HD vaccine elicited significantly greater monofunctional and polyfunctional CD4 + and CD8 + T-cell responses against influenza A/H1N1, A/H3N2, and B. For example, median vaccine-elicited influenza-specific polyfunctional CD4 + T cells were higher in recipients of the HD than SD vaccine after stimulation with influenza A/H1N1 (1193 vs 0 per 10 6 CD4 + T cells; P = .003), A/H3N2 (1154 vs 51; P = .008), and B (1102 vs 0; P = .001). Likewise, vaccine-elicited influenza-specific polyfunctional CD8 + T cells were higher in recipients of the HD than SD vaccine after stimulation with influenza B (367 vs 0; P = .002). Conclusions: Our study provides novel evidence that HD vaccine elicits greater cellular responses compared with the SD vaccine in SOT recipients, which provides support to preferentially consider use of HD vaccination in the SOT setting. Abstract : This substudy of a randomized controlled trial shows that the high-dose influenza vaccine elicits significantly better T-cell responses than the standard-dose vaccine in organ transplant patients and provides evidence that it may be the preferred vaccine in the transplant setting.